2018
DOI: 10.1098/rsfs.2017.0059
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-loaded graphene oxide flakes as an effective antibacterial system against methicillin-resistant Staphylococcus aureus

Abstract: Methicillin-resistant (MRSA) is responsible for serious hospital infections worldwide and represents a global public health problem. Curcumin, the major constituent of turmeric, is effective against MRSA but only at cytotoxic concentrations or in combination with antibiotics. The major issue in curcumin-based therapies is the poor solubility of this hydrophobic compound and the cytotoxicity at high doses. In this paper, we describe the efficacy of a composite nanoparticle made of curcumin (CU) and graphene oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 46 publications
(78 reference statements)
1
46
0
Order By: Relevance
“…GO (4 mg/mL) was purchased from GrapheneA (Spain). GO size was evaluated by atomic force microscopy (Nanowizard II JPK Instruments AG, Berlin, Germany) as previously reported [7] and GO hydrodynamic properties were measured by dynamic light scattering (DLS) using Zetasizer Nano ZS (Malvern, Herrenberg, Germany), as previously reported [18]. Drug-conjugated GO was prepared using a fixed GO concentration and incubating with drug (AMK, INH or LZD) diluted in ultrapure water.…”
Section: Go Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…GO (4 mg/mL) was purchased from GrapheneA (Spain). GO size was evaluated by atomic force microscopy (Nanowizard II JPK Instruments AG, Berlin, Germany) as previously reported [7] and GO hydrodynamic properties were measured by dynamic light scattering (DLS) using Zetasizer Nano ZS (Malvern, Herrenberg, Germany), as previously reported [18]. Drug-conjugated GO was prepared using a fixed GO concentration and incubating with drug (AMK, INH or LZD) diluted in ultrapure water.…”
Section: Go Characterizationmentioning
confidence: 99%
“…In the field of microbiology, it has been largely demonstrated that the CNMs' unique structural and chemical properties can be exploited to change interactions between cells and microorganisms. In particular, graphene oxide (GO), the bidimensional carbon allotrope enriched in oxygen functionalities, interacts and disrupts bacteria structures, and it has been proposed as an antibacterial nanomaterial, both for medical device surface coating and systemic administration purposes [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene oxide (4 mg/ml) was purchased from GrapheneA (Spain) and diluted in MilliQ RNA and DNA free water for further experiments. GO size and thickness were evaluated by atomic force microscopy (AFM) (Nanowizard II JPK Instruments AG, Berlin, Germany) as previously reported (Bugli et al, 2018). GO hydrodynamic properties and surface charge were measured by dynamic light scattering (DLS) and zeta potential analysis by means of Zetasizer Nano ZS (Malvern, Herrenberg, Germany) as previously reported (Palmieri et al, 2019).…”
Section: Go Characterizationmentioning
confidence: 99%
“…Linklater et al [2] in their paper illustrate the processes involved in bactericidal mechanisms, which are not well established at present. This is followed by a paper by Bugli et al [3], who illustrate that curcumin-loaded graphene derivatives can provide the nano-morphology in fighting methicillin-resistant bacteria. Graphene oxide is one of the most used and leading graphene derivatives and, in their paper, Verre et al [4] vividly demonstrate the effects of graphene oxide substrates in increasing gene expression of biomolecules.…”
Section: Introductionmentioning
confidence: 96%